2016
DOI: 10.1371/journal.pone.0164931
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ready-to-Eat-Cereals on Key Nutritional and Health Outcomes: A Systematic Review

Abstract: BackgroundIn many countries breakfast cereals are an important component of breakfast. This systematic review assesses the contribution of consumption of ready-to eat cereal (RTEC) to the recommended nutrient intake. Furthermore, the effects of RTEC consumption on key health parameters are investigated as well as health promoting properties of RTEC.MethodThe Cochrane Central Register of Controlled Trials, MEDLINE, EMBASE and CINAHL have been searched up till 16th of June 2015. Randomized controlled trials were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
1
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(78 citation statements)
references
References 116 publications
4
68
1
5
Order By: Relevance
“…Cho et al [13] , using data from NHANES III (the third National Health and Nutrition Examination Survey), suggested that different types of breakfast were associated with different health parameters, for example, weight. Those findings led to the examination of "types of breakfast" with different parameters, including nutrient intake [12,14] . Using more recent data from NHANES, the mean adequacy ratio of 5 shortfall nutrients (i.e., vitamin E, calcium, magnesium, potassium, and fiber) and 13 micronutrients was lowest in breakfast skippers, followed by "other breakfast" consumers, and highest in ready-to-eat cereal (RTEC) consumers [12] .…”
Section: Nutrient Contribution Of the Breakfast Mealmentioning
confidence: 99%
“…Cho et al [13] , using data from NHANES III (the third National Health and Nutrition Examination Survey), suggested that different types of breakfast were associated with different health parameters, for example, weight. Those findings led to the examination of "types of breakfast" with different parameters, including nutrient intake [12,14] . Using more recent data from NHANES, the mean adequacy ratio of 5 shortfall nutrients (i.e., vitamin E, calcium, magnesium, potassium, and fiber) and 13 micronutrients was lowest in breakfast skippers, followed by "other breakfast" consumers, and highest in ready-to-eat cereal (RTEC) consumers [12] .…”
Section: Nutrient Contribution Of the Breakfast Mealmentioning
confidence: 99%
“…In the UK, REBCs and yoghurts contribute to 15% and 16% of free sugar intake in children aged 1.5-10 years, respectively [11]. A systematic review of observational studies found that frequent consumption (>5 servings/week) of REBCs in children was associated with higher total sugar consumption [28]. It has also been a matter of controversy that these products rely heavily on marketing strategies that contradict WHO guidance.…”
Section: Introductionmentioning
confidence: 99%
“…Breakfast cereals such as porridge and muesli are also reported to contribute to more than 50% of the breakfast energy intake for the UK population [9][10][11][12]. When consumed regularly, breakfast cereals have been linked to an increase in the nutritional profile of diets, only with the exception of a high level of simple sugars associated with those ranges with a high added sugars content [13,14]. Furthermore, evidence suggests an inverse association between breakfast cereal consumption and body weight [15,16].…”
Section: Introductionmentioning
confidence: 99%